Robust Image Hashing - Venkatesan, Ramarathnam; Koon, S.-M.; Jakubowski, Mariusz; Moulin, P. (IEEE International Conference on Image Processing: ICIP 2000, 2000)
The proliferation of digital images creates problems for managing large image databases, indexing individual images, and protecting intellectual property. This paper introduces a novel image indexing technique that may be called an image hash function. The algorithm uses randomized signal processing strategies for a non-reversible compression of images into random binary strings, and is shown to be robust against image changes due to compression, geometric distortions, and other attacks. This algorithm brings to images a direct analog of Message Authentication Codes (MACs) from cryptography, in which a main goal is to make hash values on a set of distinct inputs pairwise independent. This minimizes the probability that two hash values collide, even when inputs are generated by an adversary.